Social Stigma and Suffering: Perceptions, Practices and Impacts around COVID-19 in Bangladesh - Bulbul Siddiqi; Nur Newaz Khan (South Asia Multidisciplinary Academic Journal)
The novel coronavirus (COVID-19) has become a global concern due to the unprecedented catastrophe it has brought about. Social stigma around COVID-19 has become another concern in many areas. This study employs a qualitative approach in analyzing and discussing cultural perceptions and experiences of social stigma and suffering around COVID-19 in Bangladesh. This paper argues that socio-cultural and religious practices and various new metaphors in day-to-day linguistic usage around COVID-19 created and shaped social stigma with social suffering for the suspected, infected, associated, and even recovered individuals and groups. The findings show that stigmatization around COVID-19 takes place due to fear of infection, perceived loss of social status, discrimination in social life, and exclusion from standard health services, all of which need to be addressed in health and related policies in the future.